2016
DOI: 10.1111/ajt.13798
|View full text |Cite
|
Sign up to set email alerts
|

HLA Matching at the Eplet Level Protects Against Chronic Lung Allograft Dysfunction

Abstract: Donor selection in lung transplantation (LTx) is historically based upon clinical urgency, ABO compatibility, and donor size. HLA matching is not routinely considered; however, the presence or later development of anti‐HLA antibodies is associated with poorer outcomes, particularly chronic lung allograft dysfunction (CLAD). Using eplet mismatches, we aimed to determine whether donor/recipient HLA incompatibility was a significant predictor of CLAD. One hundred seventy‐five LTx undertaken at the Alfred Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 26 publications
1
55
0
Order By: Relevance
“…In line with evidence from transplantation of other solid organs, recent studies indicate that total HLA mismatches are associated with an increased risk for CLAD (54, 62). Hayes et al described an increased risk for BOS, with HLA-A mismatches being associated with a greater hazard (54), whereas Walton et al demonstrated the importance of eplet mismatches as a risk factor for RAS (62).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In line with evidence from transplantation of other solid organs, recent studies indicate that total HLA mismatches are associated with an increased risk for CLAD (54, 62). Hayes et al described an increased risk for BOS, with HLA-A mismatches being associated with a greater hazard (54), whereas Walton et al demonstrated the importance of eplet mismatches as a risk factor for RAS (62).…”
Section: Discussionmentioning
confidence: 59%
“…Hayes et al described an increased risk for BOS, with HLA-A mismatches being associated with a greater hazard (54), whereas Walton et al demonstrated the importance of eplet mismatches as a risk factor for RAS (62). In our study, HLA mismatches were an independent risk factor of mortality in the multivariate model but not for BOS or RAS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Duquesnoy reported on HLA epitope-based matching for organ transplantation [35, 36]. Wiebe reported on epitope matching to minimize de novo donor-specific antibodies to improve transplantation outcome [37] and Walton et al reported on the usefulness of matching at the epitope level which protects against chronic lung allograft dysfunction [38]. …”
Section: Discussionmentioning
confidence: 99%
“…12,13 The eplet, however, is only one small part of the antigen surface that interacts with the antibody. A greater number of HLA eplet mismatches with the donor has been associated with an increased risk of dnDSA development.…”
Section: Introductionmentioning
confidence: 99%